Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1200/jco.2015.33.3_suppl.302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coadministered beta blocker and COX-2 inhibitor to patients with pancreatic cancer prior to receiving albumin-bound (Nab) paclitaxel.

Abstract: 302 Background: Paclitaxel protein-bound particles nab-paclitaxel plus gemcitabine is rapidly becoming the standard of care for patients with metastatic adenocarcinoma of the pancreas (mPCa). Preclinical and clinical studies of beta-blockers and NSAIDs show a benefit of these drugs in pancreatic cancer. The aim of this study was to evaluate the impact of the co-administration of the beta blocker propranolol (P) and the selective COX-2 inhibitor etodolac (E) on survival of patients with mPCa receiving GemNab a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The same group also reported on a small (n = 37) single centre open-label trial of gemcitabine and nab-paclitxel (GemNab) with and without VT-122 in patients with locally advanced or metastatic pancreatic cancer [85]. Patients in the GemNab + VT-122 arm (n = 20) were treated with VT-122 for one week prior to commencement of GemNab, and then continuously with GemNab.…”
Section: Human Datamentioning
confidence: 99%
“…The same group also reported on a small (n = 37) single centre open-label trial of gemcitabine and nab-paclitxel (GemNab) with and without VT-122 in patients with locally advanced or metastatic pancreatic cancer [85]. Patients in the GemNab + VT-122 arm (n = 20) were treated with VT-122 for one week prior to commencement of GemNab, and then continuously with GemNab.…”
Section: Human Datamentioning
confidence: 99%
“…Most importantly, a randomized investigator-initiated and prospective study on metastatic adenocarcinoma of pancreas reported that administration of propranolol and COX-2 inhibitor etodolac (PE) 1 week prior to the start of chemotherapy with nab-paclitaxel and gemcitabine (GemNab) improved progression-free survival (7.2 vs. 11.8) and overall survival (10.5 vs. 15.9 months) in comparison to GemNab treatment alone. [13] Of an interesting note, the largest retrospective cohort study on a single β-blocker that compared the effects of long-term carvedilol use (n = 6771) against nonuse (n = 6771) was recently published with median follow-up of 5.17 years, which reported significant reduction of cancer risk across all cancer sites (HR 0.74: 95% CI = 0.63-0.87, p < 0.001), with maximum risk reduction in stomach (HR 0.30: 0.14-0.63, p < 0.05) and lung (HR 0.59: 95%CI = 0.37-0.94, p < 0.05) cancers [14] (Table 2). Interestingly, it also reported insignificantly reduced risk of hematological malignancy (HR 0.67: 95%CI = 0.27-1.63), head and neck (HR 0.68: 95%CI = 0.38- Chemopotentiating effects of the β-blockers aforementioned have been also reported in numerous preclinical studies concerning conventional cytotoxins and cancer immunotherapeutics.…”
Section: Anticancer Effects Of Individual β-Blockers: Clinical and Nomentioning
confidence: 99%
“…These studies rarely assessed the effects of individual β-blockers, and the number of patients on each agent was often too small for a reliable analysis. Thus far, propranolol is the only β-blocker with individually reported clinical therapeutic utility in cancer treatment through both retrospective and randomized-prospective investigations, [12,13] although replicating studies have not been reported yet. Meanwhile, preclinical study findings thus far suggest carvedilol, nebivolol, and propranolol as promising candidate β-blockers with therapeutic effects as adjuvants to cytotoxins or immunotherapeutic treatments.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The preclinical studies presented here suggest that β-blockers could be used to complement existing chemotherapeutic strategies to improve cancer outcome in patients with pancreatic cancer [ 44 , 77 , 86 ]. While a small retrospective study did not support this concept [ 123 ], positive results were obtained in a recent prospective trial [ 124 ]. The study was a randomized, open-label, single-center clinical trial to compare the effectiveness of propranolol plus etodolac, a COX-2 inhibitor, in combination with gemcitabine plus nab- paclitaxel [ 124 ].…”
Section: Translation Of β-Blockers For the Treatment Of Pancreaticmentioning
confidence: 99%